Fertility preservation for patients with melanoma. Issue 5 (19th July 2022) - Filippi, Francesca; Serra, Nicole; Vigano, Paola; Boeri, Luca; Cimminiello, Carolina; Di Guardo, Lorenza; Somigliana, Edgardo; Del Vecchio, Michele
Abstract : The advent of immunotherapy and targeted therapy has outstandingly improved the prognosis in subjects with melanoma. Their use is now advocated also in earlier stages as an adjuvant therapy, and some neoadjuvant clinical trials are ongoing. Consequently, survivors free of disease are increasing, as well as those exposed to these new agents. Parenthood in survivors is, therefore, receiving growing interest. Evidence on the effects of immunotherapy and targeted therapy on future fertility is limited, but not entirely reassuring, in particular for immunotherapy. The necessity of delaying pregnancy seeking up to the end of treatments and follow-up (iatrogenic aging) is an additional albeit neglected source of concern, in particular for women in their late 30s. Subjects with melanoma should be informed on the multifaceted issue of future fertility at the time of cancer diagnosis. Available options of fertility preservations, including sperm and oocytes storage, should also be discussed, especially considering that at the age 0–39, melanoma represents the second most frequent neoplasia. In the decision-making process, most attention should be given to sex, age, and exposure to immunotherapy.